Determination of Thermal Activation Energy and Grain Size of Iron Hexadecachloro Phthalocyanine Thin Films - Raji Koshy; C.S. Menon (Журнал нано- та електронної фізики)
Electrical, structural and surface morphological properties of Iron hexadecachloro phthalocyanine thin films deposited onto glass substrates are studied as a function of post deposition annealing temperature in air. Organic semiconductors are extensively used in optical and electronic devices such as organic photovoltaic solar cells (OSC), thin film transistors (OTFT) and organic light emitting diodes (OLED). Metal phthalocyanines are one of the most promising candidates to be used in the fabrication of such devices. A No. of phthalocyanines have been extensively studied. But not much work have been carried out in Cl16FePc thin films. Basic characteristics of Cl16FePc are not reported in literature. Hexadecacholoro phthalocyanines have attracted interest as possible n-type organic semiconductor with high electron mobility and good stability characteristics. In the present work we investigate the activation energy of the Cl16FePc thin films as a function of air annealing temperature. We also report the film structure and surface morphology by X-ray diffraction (XRD) and Scanning electron microscopy (SEM).